Times and methods of black oat management on corn plantability - Sgarbossa, Maicon; Modolo, Alcir José; Aparecido Santos Morais, Vinicius; Dotto, Lucas; da Rocha Campos, José Ricardo; de Oliveira Vargas, Thiago (Revista Ceres, 2022)
The importance of maintaining straw on the soil surface is a subject widely discussed and proven in the literature. However, the effects of this straw on planting efficiency and quality still lack information. In this sense, both time and method of the black oat management influence the permanence of the straw on the soil and, thus, can interfere in the next crop’s germination and plantability of the seed drill. This study aimed to evaluate methods and times of black oat management and their implications on the plantability and development of the corn crop in succession in two harvests. A randomized block design with twelve treatments was used, consisting of the combination of three methods of management (crushed, rolled, and desiccated) and four times of management (0, 10, 20, and 30 days before the corn sowing) of black oat straw, arranged in a 3 x 4 factorial scheme, with four replications. The black oat management carried out 30 days before the corn sowing provides the highest corn emergence rate. Management methods that promote greater fragmentation of straw tend to offer less mechanical impediment to seedling development and result in a greater initial and final plant population.